2023
DOI: 10.1002/anie.202308980
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐to‐H2O2 Catalyzed by Covalent Organic Frameworks

Zijun Yong,
Tianyi Ma

Abstract: Benefiting from the excellent structural tunability, robust framework, ultrahigh porosity, and rich active sites, covalent organic frameworks (COFs) are widely recognized as promising photocatalysts in chemical conversions, and emerged in the hydrogen peroxide (H2O2) photosynthesis from 2020. H2O2, serving as an environmental‐friendly oxidant and a promising liquid fuel, has attracted increasing researchers to explore its potential. Over the past few years, numerous COFs‐based photocatalysts are developed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(35 citation statements)
references
References 131 publications
(154 reference statements)
1
34
0
Order By: Relevance
“…All the CB potentials were lower than the redox potential of O 2 /H 2 O 2 while all the valence bands (VB) were higher than the redox potential of H 2 O 2 /H 2 O, indicating that all TpBpy (HAc), TpBpy (IL), HRP@TpBpy (HAc) and HRP@TpBpy (IL) were thermodynamically favorable for the photosynthesis of H 2 O 2 from H 2 O and O 2 . Indeed, both TpBpy (IL) and TpBpy (HAc) frameworks showed the desirable photocatalytic synthesis of H 2 O 2 under xenon lamp irradiation (λ>400 nm; light intensity at 400–700 nm: 550 W m −2 ), and the ERP experiment demonstrated that ⋅OH and ⋅OOH were the main intermediate species participating in the generation of H 2 O 2 (Figure S51), well agreement with the previously reports [45–47,49] . Interestingly, based on the peroxidase chromogenic method for H 2 O 2 quantification (Figure S52), TpBpy (IL) exhibited 1.55‐fold H 2 O 2 production ability compared to TpBpy (HAc) (Figure 6c).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…All the CB potentials were lower than the redox potential of O 2 /H 2 O 2 while all the valence bands (VB) were higher than the redox potential of H 2 O 2 /H 2 O, indicating that all TpBpy (HAc), TpBpy (IL), HRP@TpBpy (HAc) and HRP@TpBpy (IL) were thermodynamically favorable for the photosynthesis of H 2 O 2 from H 2 O and O 2 . Indeed, both TpBpy (IL) and TpBpy (HAc) frameworks showed the desirable photocatalytic synthesis of H 2 O 2 under xenon lamp irradiation (λ>400 nm; light intensity at 400–700 nm: 550 W m −2 ), and the ERP experiment demonstrated that ⋅OH and ⋅OOH were the main intermediate species participating in the generation of H 2 O 2 (Figure S51), well agreement with the previously reports [45–47,49] . Interestingly, based on the peroxidase chromogenic method for H 2 O 2 quantification (Figure S52), TpBpy (IL) exhibited 1.55‐fold H 2 O 2 production ability compared to TpBpy (HAc) (Figure 6c).…”
Section: Resultssupporting
confidence: 86%
“…Crystalline COF skeleton means that the molecular tectons are orderly linked and this favors the formation of large π‐conjugated networks, holding attractive photoelectric attributes which cannot be attained in the amorphous polymer [45–47] . It is plausible that the spatial integration of enzymatic catalysis and the photoelectric effect of the COF skeleton in our enzyme@COF (IL) system may encourage new applications.…”
Section: Resultsmentioning
confidence: 99%
“…The thermogravimetric analysis results reveal that decomposition temperature of 1D PyTTA‐COF reaches 516 °C, which is significantly higher than that of 2D counterpart (486 °C, Figure S3). Meanwhile, 1D PyTTA‐COF displays good chemical stability, which can retain high crystallinity after immersing them in N,N‐Dimethylformamide (DMF), tetrahydrofuran (THF), dichloromethane (DCM), hydrochloric acid (HCl, pH=1), sodium hydroxide (NaOH, pH=13) for 24 h (Figure S3b) [46] …”
Section: Resultsmentioning
confidence: 99%
“…1–3 The abundant building units and various synthesis methods greatly enrich the diversity of COFs. 4–8 As potential materials, numerous applications including energy storage, 9–11 sensing, 12–14 adsorption, 15–18 and catalysis 19–23 have been developed based on COFs. Equipped with adjusted band positions and functionalized skeletons, COFs with inherent porosity are outstanding materials for efficient photocatalysis.…”
Section: Introductionmentioning
confidence: 99%